IHYA' AL-MAWAT'S RESISTANCE TO LAND LEGAL POLICY IN INDONESIA - Abidin, Abidin; Suryanto, Tulus; Aslam, Mohd Mizan (Fakultas Hukum, Universitas Diponegoro, 2024)
The purpose of this study is to map and examine the manifestations, contributing elements, and ramifications of iḥyā' al-mawāt opposition to Indonesian land laws. Utilizing a qualitative-objectivity approach, the findings from material and interviews are positioned. The research results show that there has been iḥyā' al-mawāt resistance to land law policies in Indonesia due to prohibitions on use, management and ownership even though the goals are the same, namely community welfare and legal certainty over land. The factors causing resistance are based on the desire to prosper the earth, increase welfare, legal certainty, and resolve land legal relations with others. Open resistance was carried out in the form of demonstrations against state land control. Offering and enforcing the concept of iḥyā' al-mawāt continually, expressing irritation and curses in one's heart without showing it to others, and crying in private are all examples of closed resistance. Clever revenge plotting is another way that closed resistance is demonstrated. The action of iḥyā' al-mawāt resistance that must be taken against land law policy in Indonesia is the granting of rights to use and even own ownership of land resulting from the community's iḥyā' al-mawāt in a professional.